Contextualized Low-Tech Blended Learning for EFL Instruction in Remote Island Schools: A Classroom Action Research at SMP Negeri Tiakur, Indonesia - Kamanasa, Louisa Sarah; Meyer, Fredi; Maruanaya, Hendrik Jacob; Keiwury, Nely (Koli Journal : English Language Education, 2025)
This study demonstrates that a low-tech blended learning model, which integrates locally contextualized video materials and Google Classroom, can significantly improve English grammar achievement among junior high school students in a remote island context. At SMP Negeri Tiakur in Maluku Barat Daya, Indonesia, a single-cycle classroom action research intervention with thirteen eighth-grade students resulted in a 51.8% mean score increase (from 4.46 to 6.77) and enhanced engagement, motivation, and digital adaptability. To better contextualize this improvement, the 51.8% gain in mean scores translates to an effect size above the general educational 'hinge point' of 0.40, as proposed by John Hattie, indicating a practically significant impact on learning outcomes. Most students (89%) indicated that blending cultural content with technology made English learning more meaningful and accessible. These findings reinforce the view that the impact of digital pedagogy depends on meaningful contextual integration rather than technological sophistication. The study contributes to understanding how culturally grounded, low-tech blended learning can empower learners in underserved educational environments.